2017
DOI: 10.1007/s13318-017-0431-0
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Busulphan Concentrations in Children Undergone Hematopoietic Stem Cell Transplantation: Unicentric Experience over 10 years

Abstract: We concluded that older age at HSCT, intravenous administration of busulphan, cumulative, and prescribed dose of busulphan are associated with higher AUC levels. The absence of significant correlations between toxic events, graft failure, and AUC suggests the efficacy of busulphan concentrations monitoring in our patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Nine [13-17, 23, 24, 26, 29] were prospective studies and four [2,20,25,27] were retrospective studies. Six studies were conducted in Europe [14,16,20,24,25,27], six studies were in United States [2,13,15,17,26,29] and one [23] was in Japan. Bu concentrations were measured by high-performance liquid chromatography by means of ultraviolet detection [23,29], while the remainder [2, 13-17, 20, 24-27] were measured by gas chromatography with mass spectrometry detection.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine [13-17, 23, 24, 26, 29] were prospective studies and four [2,20,25,27] were retrospective studies. Six studies were conducted in Europe [14,16,20,24,25,27], six studies were in United States [2,13,15,17,26,29] and one [23] was in Japan. Bu concentrations were measured by high-performance liquid chromatography by means of ultraviolet detection [23,29], while the remainder [2, 13-17, 20, 24-27] were measured by gas chromatography with mass spectrometry detection.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The quality assessment of the included studies is presented in Supplementary Table S5. Overall, the subjects included were representative, and ascertainment of exposure was confirmed by secure record, six studies were comparable on basis of main factors [2, 14-16, 24, 25], and seven studies were comparable on two or more factors [13,17,20,23,26,27,29]. Outcome assessment was based on pharmacy and medical records, the follow-up period was sufficient for outcomes to occur, and adequacy of follow-up of cohorts.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous observational studies have recommended target Bu exposure ranges at different cut-off values, including 900 [2,[12][13][14][15][16][17], 1000 [18], 1225 [11], 1350 [15][16][17], 1500 [14] and 1575 [11] µM × min for every 6-hour dosage. On the contrary, some observational studies found no statistically significant differences in transplant-related toxicity (TRT) or graft failure rate between different Bu AUC [19][20][21].…”
Section: Introductionmentioning
confidence: 99%